Solace - Caverly, Tim; Manzo, Franklin ([Place of publication not identified] : [publisher not identified], 2019)
During his third year of college Jim is forced to abandon school. He returns to the family farm only to face one hardship after another. Then one day Jim discovers an envelope-yellowed with age. The letter instructs Jim to go to Allagash Lake and retrieve an heirloom "for the sake of the family."
This printing contains corrections of the original version.
Maine author.
Keywords: Allagash River (Me.) -- Fiction; Maine -- Fiction